An atomic force microscopy study of Eurofer-97 steel - Stamopoulos, D.; Aristomenopoulou, E.; Sandim, M.J.R.; Sandim, H.R.Z.; Pissas, M. (JEMS 2013 - JOINT EUROPEAN MAGNETIC SYMPOSIA, 2014)
In recent years the microstructure, mechanical and magnetic properties of Eurofer-97 steel are studied intensively due to its application in nuclear fusion power plants. Its microstructure is usually accessed by means of electron microscopy. Here we present an alternative approach utilizing Atomic Force Microscopy (AFM) to study as-received Eurofer-97 steel. We recorded both the Height Signal (HS) and Phase Signal (PS) that provided information on the morphologic and inelastic topography, respectively. With the HS we detected spherical particles (SPs) of size 50-2000 nm. Interestingly, micrometer SPs (0.1-2.0 mu m) are randomly distributed, while nanometer SPs (50-100 nm) are sometimes arranged in correlation to grain boundaries. The PS clearly revealed that the micrometer SPs exhibit inelastic properties. Though we cannot identify the elemental composition of the SPs with AFM, based on relevant electron microscopy data we ascribe the nanometer ones to the TaC, TiN and VN and the coarse micrometer ones to M23C6 (M=Cr, Fe). The latter class of SPs can probably be active sites that influence the mechanical properties of Eurofer-97 steel upon annealing as observed in relevant electron microscopy based studies.